Initial evolution of elderly intelligence studies: myths and reality - Rozestraten, Reinier Johannes Antonius (2002)
This paper presents the beginning and the first development of studies about the intelligence of the aged within the frame of the five phases of behavior psychogenesis: Information intake, information processing, decision making, response-behavior and feedback. In the course of this evolution that starts at the end of World War I, three myths emerged that successively were refuted: a) the myth that intelligence is a unique massive capacity instead of a joint of several capacities which may combine in multiple forms; b) the myth that this unique intelligence in its totality deteriorates during old age, but later was verified that only some capacities named "fluid intelligence" are affected meanwhile others characterized as "crystallized intelligence" are constant or even improved; e c) the old age factor is the unique factor that influences the development or deterioration of intellectual capacities. To this last myth Lehr asserts that there are at least more nine influencing factors: Decline of the G factor , speed, innate aptitude, educational level, training, stimulating environment, health, successful life and motivation.